1973
DOI: 10.2135/cropsci1973.0011183x001300030005x
|View full text |Cite
|
Sign up to set email alerts
|

Pollen Germination and Tube Growth after Selfing and Crossing Coronilla varia L1

Abstract: Crownvetch, Coronilla varia L., is relatively self‐incompatible. Plants selected to represent the full range of self‐fertility of a large sample of C. varia L. ‘Penngift’ were used in greenhouse experiments to locate the site or sites of incompatibility of self‐pollinations. Pollen germination and pollen tube growth in pistils after self‐ and cross‐pollinations were observed employing UV fluorescence microscopy.Pollen germination on the stigma and pollen tube penetration of the style occurred within the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1976
1976
2002
2002

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…In Coronilla varia for example, Baluch, Risius and 152 iV;i-M. SEDGLEY >V •.. Cleveland (1973) observed occasional instances where two tubes entered an ovule and Ter-avanesjan (1949) noted sixty to eighty tubes entering the ovary of a Gossypium hirsutum flower although only thirty ovules are generally present. On the other hand Ockendon and Gates (1975) observed a reduction in number of tubes reaching the ovary to a figure lower than the usual number of ovules in Brassica oleracea.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In Coronilla varia for example, Baluch, Risius and 152 iV;i-M. SEDGLEY >V •.. Cleveland (1973) observed occasional instances where two tubes entered an ovule and Ter-avanesjan (1949) noted sixty to eighty tubes entering the ovary of a Gossypium hirsutum flower although only thirty ovules are generally present. On the other hand Ockendon and Gates (1975) observed a reduction in number of tubes reaching the ovary to a figure lower than the usual number of ovules in Brassica oleracea.…”
Section: Discussionmentioning
confidence: 98%
“…Pistils were collected 18 h after pollination and squashes stained with Aniline.Blue were prepared according to the method of Martin (1959) as modified by van Hal and Verhoeven (1968). (Preparations from pistils collected between 6 and 30 h after pollination did not differ from those taken after 18 h.) The preparations were observed using a Zeiss Photomicroscope II with reflected light from an HBO 100 high pressure mercury vapour lamp, BG3 exciter filter and 65/50 harrier filter comhination.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Baluch et al (1973), working with Coronilla varia L., and Socías i Company (2001), studying almond, showed that pollen tube behaviour was the same under these conditions as in pistils of non-excised branches of potted plants or trees in the field. Moreover, this method allows one to work under controlled conditions (particularly important for temperature) for all cultivars during the assay.…”
Section: Discussionmentioning
confidence: 99%
“…This may be caused by several phenomena such as an acceleration of growth rate of the slower pollen tubes in the basal part of the style, a retardation of growth of the rapid tubes or both, or differences in penetration capacities of the ovary, the ovule or the embryosac. Such different selective barriers have also been suggested in Coronillu (BALUCH et al, 1973). Maybe the self pollen and/or the foreign pollen send a signal downwards to basal parts of the style or the ovary to block or retard the passage of the first arriving pollen tubes (often from the self pollen) enabling the later arriving pollen tubes (often from the foreign pollen) to overcome the time handicap and to fuse with the egg-tel.…”
Section: And Conclusionmentioning
confidence: 88%